2000
DOI: 10.1001/archotol.126.5.652
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism After Treatment for Nonthyroid Head and Neck Cancer

Abstract: Approximately 15% of patients treated for advanced head and neck cancer with surgery and radiotherapy will develop hypothyroidism. Those treated with total laryngectomy and radiotherapy are at greatest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 20 publications
9
108
0
3
Order By: Relevance
“…Posner et al 7,9 examined the effect of combination chemotherapy on hypothyroidism in patients with head and neck carcinoma and found no association. Similarly, Weissler and Berry 25 and Sinard et al 26 reported no increase in the incidence of hypothyroidism in patients with head and neck carcinoma who were treated with chemotherapy, an observation that was confirmed in our series. However, Hancock et al 23 reported that chemotherapy was a significant risk factor for the development of hypothyroidism after radiation therapy in patients with Hodgkin disease.…”
Section: Discussionsupporting
confidence: 89%
“…Posner et al 7,9 examined the effect of combination chemotherapy on hypothyroidism in patients with head and neck carcinoma and found no association. Similarly, Weissler and Berry 25 and Sinard et al 26 reported no increase in the incidence of hypothyroidism in patients with head and neck carcinoma who were treated with chemotherapy, an observation that was confirmed in our series. However, Hancock et al 23 reported that chemotherapy was a significant risk factor for the development of hypothyroidism after radiation therapy in patients with Hodgkin disease.…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of autoimmune thyroid diseases, including Hashimoto's thyroiditis [16,17], Graves' disease [3][4][5][6] and Graves' ophthalmopathy [4], in patients who have received external radiation therapy is significantly higher than that in untreated controls. Indeed, patients who have received external radiation to the cervical region are more likely to have antithyroid antibodies than are untreated patients [17], and the titers of antithyroid antibodies are elevated after radiation therapy [18]. In our case, various autoimmune antibodies, including TSAb, TgAb and TPOAb, were detected at the onset of Graves' ophthalmopathy.…”
Section: Discussionmentioning
confidence: 57%
“…It rises to 28% when accompanied with surgery and 35-65% when associated with hemithyroidectomy. [13][14][15] The incidence in those who undergo total laryngectomy with ipsilateral hemithyoidectomy, is around 44-89%. [16][17][18][19][20] This is due to surgical manipulation or radiation therapy causing disruption of gland vascularity or immune mediated response to radiotherapy as evidenced by the elevated levels of anti thyroglobin and or antimicrosomal antibody titres.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] This is due to surgical manipulation or radiation therapy causing disruption of gland vascularity or immune mediated response to radiotherapy as evidenced by the elevated levels of anti thyroglobin and or antimicrosomal antibody titres. 13 The time of onset of hypothyroidism in post treated T4 hypopharyngeal and laryngeal cancers is 42 days versus 110 days in salvage and primary cases respectively.…”
Section: Discussionmentioning
confidence: 99%